Biosensing enhancement of dengue virus using microballoon mixers on centrifugal microfluidic platforms - Aeinehvand, Mohammad Mahdi; Ibrahim, Fatimah; Harun, Sulaiman Wadi; Djordjevic, Ivan; Hosseini, Samira; Rothan, Hussin Alwan; Yusof, Rohana; Madou, Marc J. (Elsevier, 2015)
Dengue is the current leading cause of death among children in several Latin American and Asian countries. Due to poverty in areas where the disease is prevalent and the high cost of conventional diagnostic systems, low cost devices are needed to reduce the burden caused by dengue infection. Centrifugal microfluidic platforms are an alternative solution to reduce costs and increase the availability of a rapid diagnostic system. The rate of chemical reactions in such devices often depends on the efficiency of the mixing techniques employed in their microfluidic networks. This paper introduces a micromixer that operates by the expansion and contraction of a microballoon to produce a consistent periodical 3D reciprocating flow. We established that microballoons reduced mixing time of 12 mu l liquids from 170 min, for diffusional mixing, to less than 23 s. We have also tested the effect of the microballoon mixers on the detection of the dengue virus. The results indicate that employing a microballoon mixer enhances the detection sensitivity of the dengue virus by nearly one order of magnitude compared to the conventional ELISA method. (C) 2014 Elsevier B.V. All rights reserved.